Metodología de soporte y mantenimiento para los equipos que intervienen el monitoreo de variables del sistema de alertas tempranas del Proyecto Hidroeléctrico Ituango - Peña Caicedo, Deiby (Universidad Antonio Nariño, 2021)
Two years after the closure of the Auxiliary Deviation Gallery, which led to the contingency of the Hidroituango project, in the north of Antioquia; Empresas Públicas de Medellín reported that it has made significant progress in the recovery of the power house, the place where it is expected by 2024, to generate 2,400 megawatt hours, which will deliver energy to 8 million homes in the country (Ramirez, 2020). The flow through the Power House stopped in February 2019, when the last gate that allowed the flow to pass through the cavern closed. During several weeks, alerts were presented due to the appearance of sinkholes that could compromise the stability of the massif, however, such alerts were overcome and in later months, the cavern was entered to determine the current state of the Power House, its infrastructure. and their teams (Villamil, 2019, p. 91).